Effects of Injection of Carbon Nanotubes on EEG and Results of a Behavioral Test in Rats - Azimirad, V.; Hosseinpour, M.; Shahabi, P.; Alimohammadi, M.; Sadighi, M.; Hatami, H. (Нейрофизиология, 2015)
We examined the biocompatibility of carbon nanotubes (CNTs) injected i.p. into rats (1 mg/kg body mass) by recording EEG from the frontal and occipital cortex and performing the water maze router test before and after such injection. For EEG, the energy and average power spectral density of wavelet coefficients in the β, α, and θ bands were considered the features. In the water maze router experiment, the distance, time, and speed of rats were investigated as behavioral factors. Comparison of EEG signals before and after injection showed that introduction of CNTs exerted no significant effect on electrophysiological brain indices. A comparison of behavioral factors before and after injection, however, showed that injections of CNTs increased the pacing distance and time to find the desired platform and decreased somewhat the speed in the water maze router experiment. A possible reason of this phenomenon is the possible influence of CNTs on ion fluxes in brain neurons.